(untitled) (Research, Society and Development, 2020)
The camu-camu (Myrciaria dubia (H.B.K.) Mc Vaugh) whose fruit is widely cultivated in the Peruvian Amazon region. The objective of this work was to study the fruit pulp in three stages of maturity, submitted to ultrasound, vacuum concentration, vacuum packing, freezing at -20ºC, and to study the effects on its bioactive components, molds and yeasts. Camu camu pulp, which presented the highest content of bioactive components (ripe state) was subjected to ultrasonic treatment at 40 KHz with time 0, 1, 3, 5, 7 and 10 minutes. The values were ascorbic acid (2151 ± 16 mg x 100 g-1), total polyphenols (739 ± 24 mg x 100 g-1) and antioxidant capacity as ABTS (IC50 = 2.94 ± 0.11 μg x mL-1) and DPPH (IC50 = 7.43 ± 0.12 μg x mL-1). The method of concentration under vacuum and frozen at -20°C for 90 days increased the level of ascorbic acid by 207.17 % due to its 50% concentration, reaching a total loss of polyphenols in the third month of storage of only 6.6 % of its initial zero time content. When we treated the fresh pulp with ultrasound, the 5-minute ultrasound was chosen for storage for 120 days at -20ºC and an increase in antioxidant capacity of 20.5% for total polyphenols, 2% for ABTS and 23% for DPPH was observed with respect to the untreated pulp. We conclude that the treatment with ultrasound, vacuum concentration and freezing, increases conservation time, little loss of antioxidant capacity increases its reduction capacity.